New Contexts for Professional Learning: Analyzing High School Science Teachers' Engagement on Twitter. (December 2019) - Fischer, Christian; Fishman, Barry; Schoenebeck, Sarita Yardi
This mixed-methods observational study analyzes Advanced Placement (AP) Biology teachers' engagement in microblogging for professional learning. Data from three hashtag-based Twitter communities—#apbiochat, #apbioleaderacad, and #apbioleaderacademy (121 users; 2, 253 tweets)—are analyzed using educational data mining, qualitative two-cycle content analysis, social network analysis, linear and logistic regression analyses, and hierarchical linear modeling. Results indicate that teachers' use of Twitter reflects aspects of high-quality professional development. Notably, Twitter's nonhierarchical organization affords shared content creation and distribution. Additionally, Twitter allows for different temporal participation patterns and supports the personalization of learning experiences aligned to teachers' needs and preferences. Furthermore, teachers frame their interactions on Twitter positively—thus, creating a supportive environment for professional learning that might reduce perceived professional isolation. Based on this analysis, policymakers and school leaders should feel comfortable encouraging teachers to use microblogging as part of their professional learning activities.